ATLAS: Internet of Things Platform for Precision Aquaculture - Papanikolaou, Vasilis K.; Tegos, Sotiris A.; Bouzinis, Pavlos S.; Tyrovolas, Dimitrios; Diamantoulakis, Panagiotis D.; Karagiannidis, George K. (2022 Panhellenic Conference on Electronics and Telecommunications, PACET 2022, 2022)
The rapid growth of fish farming and production has led to the need for precision aquaculture. Concurrently, emerging cutting-edge technologies such as Internet of Things (IoT), cloud services, and artificial intelligence (AI) promise to overcome the challenges in fish farming and provide continuous monitoring, data analytics, and decision-making. In this work, we propose the ATLAS IoT platform which is designed specifically in order to meet the demands of precision aquacultures. More specifically, the ATLAS architecture is presented with its respective components, which are notated as the architecture's layers and they are described in detail. The ATLAS platform utilizes the synergy of IoT, cloud services, AI, and data analytics in order to capture the heterogeneous requirements of an automated aquaculture monitoring system. The latter entails the data collection, the data transfer, the design of communications schemes, energy efficiency provision, intelligent services, the pro-active decision making, and, finally, the creation of a user interface. Ultimately, the amalgamation of the aforementioned components creates the ATLAS platform, whose goal is to optimize the fish farming procedures.
Created from Fastlane, Scopus look-up
Keywords: data analytics; Internet of Things (IoT); precision aquaculture; system architecture